Moderasi Beragama Dalam Mendudukkan Posisi Perempuan Dalam Rumah Tangga - Efa Rodiah Nur; Agus Hermanto; Mufid Arsyad (Saintifika Islamica, 2022)
Religious moderation is a perspective, attitude, and practice in common life by embodying the essence of religious teachings towards the principle of justice. This study aims to see how religious moderation is in positioning women in the household. The research was carried out using library research. Data collection techniques by collecting various sources including articles, books, Al-Qur'an, and hadith. Data analysis by providing a re-interpretation of the verses and the paradigm of society that is gender biased. The results of the study show that women in the current context must have an appropriate position in realizing their rights in the household, so that their position in a moderate way can build mutual values in the household in a way that is fair, balanced, equal, democratic and treats both of them equally good way.